2021
DOI: 10.1016/j.ijid.2020.10.098
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 hospital outbreaks: Protecting healthcare workers to protect frail patients. An Italian observational cohort study

Abstract: Highlights This study included 3570 healthcare workers underwent naso and oropharyngeal swabs. The workers were divided into two groups based on COVID-19 patient contact type. SARS-CoV-2 infection prevalence is 0.45% (25 workers of 5750 subjected to protocol). We found 0.52% positive in the low-risk group, 13.16% in the high-risk group. Prevention procedures reduce the risk related to SARS-CoV-2 for healthcare workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 17 publications
(22 reference statements)
1
37
0
5
Order By: Relevance
“…Work-related factors may play a crucial role in exacerbating the effects of the pandemic isolation measures on people's mental well-being. Healthcare workers, especially those on the frontline, migrant workers, and workers in contact with the public are among the most affected with psychological critical issues in the workplace (3)(4)(5). Job insecurity and future uncertainty are significantly contributing to this "psychological pandemic" (3).…”
Section: Introductionmentioning
confidence: 99%
“…Work-related factors may play a crucial role in exacerbating the effects of the pandemic isolation measures on people's mental well-being. Healthcare workers, especially those on the frontline, migrant workers, and workers in contact with the public are among the most affected with psychological critical issues in the workplace (3)(4)(5). Job insecurity and future uncertainty are significantly contributing to this "psychological pandemic" (3).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common clinical symptoms of COVID-19, fever, dyspnea, asthenia, cough, anosmia, and dysgeusia are listed as well as few gastrointestinal symptoms, headache, and sore throat, leading in the most severe cases to acute respiratory distress syndrome with bilateral interstitial acute pneumonia, multiple organ failure, and death [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A study showed that chilblains, urticaria, and tremors have been reported as associated symptoms of the patient with COVID-19 [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the University Hospital of Bari (Apulia Region, Southern Italy), the enhancement of preventive measures, the design of a reporting system, and the implementation of measures of preventive isolation (COVID-19 Hotel) reduced the prevalence of infection among HCWs [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%